Microring resonator based photonic devices using high-contrast waveguides - Darmawan, Stevanus (2009)
Photonics as a field began in the 1960s with the invention of laser. The inventions of semiconductor laser diode in the 1970s and Erbium-doped fiber amplifier (EDFA) in the late 1980s have revolutionized the telecommunication of the late 20th century and provided the infrastructure for the internet worldwide. The evolution of photonics follows the path of electronics, which is towards device miniaturization and integrated circuits (IC). However, Photonic Integrated Circuits (PIC) has developed much more slowly than the Electronic Integrated Circuit (EIC), since PIC involves many more diverse devices each with different and often contrasting requirements. The various devices form important building blocks used to realize even more complex circuits which may perform wider range of functionalities on optical signals used in various applications, such as optical communication, instrumentation, sensing, and signal processing. Some of these circuits, mainly based on passive devices, are the subject of this thesis, although some theoretical works on their active applications are also included. In this thesis, we introduce and develop many photonic devices with concepts derived from basic building blocks such as directional couplers (DC), multi-mode interferometers (MMI), Mach-Zehnder interferometers (MZI) and microring resonators (µRR). These devices are used in a wide range of applications from switches to sensors. The thrust of the research is to combine these building blocks in novel ways that tap their synergistic interactions to achieve innovative circuit configurations with improved performance and functionality.